Prevalence of Geohelminth Eggs Associated with Selected Fruits and Vegetables in Gombe Metropolis - Ahmad Magaji, Musa; Abdullahi Kafarati, Jamilu; Rabi’u, Ibrahim; Abubakar, Binta (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This study was conducted to determine prevalence of geohelminths eggs associated with selected fruits and vegetables in Gombe metropolis. A cross sectional study was carried out with a total of 400 fruit and vegetable samples was collected within two periods between March-April 2020 and August-September 2020. Floatation techniques was used to recover the Nematode and Cestode eggs and were identified based on their morphological characteristics using atlas of Medical Helminthology and Protozoology. Four helminth species were discovered; Ancylostoma duodenale, Ova of Ascaris lumbricoides, Ova of Trichuris Trichiura and Strongyloides stercoralis. Gombe main market has the highest prevalence of geohelminth eggs on fruits and vegetables while least prevalence of geohelminth eggs was recorded in Gabukka market However, dry season have the lowest prevalence than the raining season. This research recommends periodic de-worming of all individuals consuming fruits and vegetables at a regular intervals and consumers of such fruits and vegetable should always wash with vinegar and salt before consumption respectively. All vendors of fruits and vegetables should be educated on the risk associated with contamination of geohelminth eggs and improvement of sanitary facilities and promoting safe disposal of waste is strongly emphasized.